Strategies for Requalification of Historic Military Sites: The Case of the Defensor Perpétuo Fort in Paraty - Lao, Milena; Arriagada, Carlos A. Hernández; Vieira, Julia Colauto; Manzo, Rafael; Costa, Beatriz Pizzato Angi (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – Analyze the state of conservation of the Defensor Perpétuo Fort in Paraty, Rio de Janeiro, identifying its main structural and heritage weaknesses, with the aim of proposing effective preservation and revitalization strategies that reconcile the protection of historical heritage with its sustainable use.Methodology – The research will be conducted using a qualitative approach, with an exploratory and descriptive nature. The qualitative methodology allows us to understand not only the technical aspects of the fort's conservation, but also the cultural, historical, and social meanings attributed to it. This approach makes it possible to interpret the interrelationships between the built heritage, the coastal environment, and the experience of the local population, respecting the uniqueness of the Paraty context. Originality/Relevance –The study addresses the relationship between historical heritage and the environment in Paraty, highlighting how the interaction between culture and nature is still largely unexplored in an integrated manner in academic literature. Its relevance lies in broadening the debate on urban conservation and revitalization from a multidisciplinary perspective, contributing to the understanding of new preservation strategies that unite cultural identity, environmental sustainability, and local development.Results – The research is expected to contribute to a better understanding of the threats to the preservation of Forte Defensor Perpétuo and to the formulation of effective conservation strategies. The diagnosis obtained may serve as a basis for future architectural and urban planning interventions, being useful for historical and environmental heritage preservation agencies. Theoretical/Methodological Contributions – The study highlights the need to understand heritage as part of an integrated urban-environmental system. The research demonstrates the relevance of an interdisciplinary approach, combining documentary analysis and territorial observation, to support strategies that reconcile cultural conservation and sustainability.Social and Environmental Contributions – The study aims to demonstrate that heritage preservation in Paraty is intrinsically linked to the protection of ecosystems and integration with the city's culture and population. The conservation of green areas, which act as a natural protective barrier for historical assets, reduces their vulnerability to climate change.
Keywords: Requalification strategies; Maritime heritage; Military architecture; Fortifications